Exploring biophilic building designs to promote wellbeing and stimulate inspiration - Yangang Xing; Nikki Stevenson; Carolyn Thomas; Alex Hardy; Andrew Knight; Nadja Heym; Alex Sumich (PLoS ONE, 2025)
Biophilic designs aim to promote health and wellbeing by incorporating nature-based features into internal and external built environments. Three theories have previously been proposed (i.e., Recovery, Attention Restoration, Refuge, and Prospect) regarding the impact of biophilic features on psychological and physiological health, but with little empirical evaluation. This current study tests these three existing theories, alongside a novel biophilic theory proposed in this paper, as that biophilic environments stimulate inspiration. A public survey was conducted, and participants completed an online stress-induction task followed by images of building interiors that systematically varied in perceived biophilic quality—ranging across four levels (from 0 = no clear biophilic features to 3 = very high biophilic features). Participants rated their psychological states associated with each of the proposed theories before and after each trial’s stress-induction and biophilic phases. Results support a positive effect of exposure to biophilic design on self-reported psychological states (including inspiration), whilst designs without biophilic quality tended to have an adverse effect on psychological states. Furthermore, findings support the extension of the current three theories to include the impact of biophilic designs on stimulating inspiration.